Adoption Status of Improved Crop Production Practices in Bt-cotton in Sri Muktsar Sahib, Punjab (Indian Journal of Extension Education, 2021)
The present study was conducted to investigate the adoption status of crop production practices in Bt cotton in Sri Muktsar Sahib District of Punjab. The data were collected from 140 cotton growers through personal interviews during two consecutive years (2016-17 and 2017-18). These data analysis revealed that area under Bt-cotton increased by 10.9 per cent in 2017-18, compared with 2016-17. A large majority ( 80%) of farmers ensured cotton sowing in the recommended time period, with the use of 900-1100 g acre-1 seed rate. This survey showed that farmers did not prefer soaking of seed and refugia in the study region. These results highlight that 65 per cent of farmers were applying fertilizer-N as per recommended rate, while 30 per cent farmers were applying fertilizer-P as per recommendation. These (57% of total farmers) farmers were applying 5 irrigations to cotton, while 7 irrigations were applied by only those farmers who had very light textured soils. A great majority of farmers ( 83%) were using manual method for weed control in Bt-cotton, and 44.0 per cent were using 3-5 sprays for management of sucking pests. The seed cotton yield of Bt cotton prominent hybrids varied from 17.5- 23.5 q ha-1, with a mean 19.4 q ha-1. These results highlight the need of intensified extension efforts to disseminate the technology developed for efficient nutrient, water and insect-pest management for yield maximization in Bt-cotton in Sri Muktsar Sahib District of Punjab.